Information fusion-based storage and retrieve algorithms for WSNs in disaster scenarios - Xiao, Zhe (2013)
Sensor networks are especially useful in catastrophic or disaster scenarios such as abysmal sea, floods, fires, or earthquakes where human participation may be too dangerous. Storage technologies take a critical position for WSNs in such scenarios since the sensor nodes may themselves fail unpredictably, resulting in the loss of valuable data. This paper focuses on fountain code-based data storage and recovery solutions for WSNs in disaster scenarios. A review on current technologies is given on challenges posed by disaster environments. Two information fusion-based distributed storage (IFDS) algorithms are proposed in the “few global knowledge” and “zero-configuration” paradigm, respectively. Correspondingly, a high-efficient retrieve algorithm is designed for general storage algorithms using Robust Soliton distribution. We observe that the successful decoding probability can be provisioned by properly selecting parameters—the ratio of number of source node and total nodes, and the storage capacity M in each node.